2020
DOI: 10.3389/fmed.2020.00267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Memory Problems Post-stroke on Patients and Their Family Carers: A Qualitative Study

Abstract: Background: Memory problems post-stroke are common and for some, these problems could then progress to a dementia illness. Once in the community, stroke-survivors are looked after by their family doctors although there is evidence that these patients may struggle to access appropriate help in the community for these problems. Although a stroke-survivor may be physically capable of performing daily tasks, they and their families may have to learn to manage and adapt to their new memory deficits. There is often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This support reduces emotional distress in stroke patients and allows them to positively embrace trauma experiences and implications [10,15,18]. For stroke patients with limited performance in their daily lives, families, as an important resource that most directly provides help after discharge, stimulate patients' rehabilitation motivation for disease relief and recovery [19,20]. In this study, family support and cognitive function in acute stroke patients were significantly correlated, which can be interpreted to mean that family support can enhance the recovery of a patient from both physical dysfunction and cognitive dysfunction based on the belief and trust gained from those around him.…”
Section: Discussionmentioning
confidence: 99%
“…This support reduces emotional distress in stroke patients and allows them to positively embrace trauma experiences and implications [10,15,18]. For stroke patients with limited performance in their daily lives, families, as an important resource that most directly provides help after discharge, stimulate patients' rehabilitation motivation for disease relief and recovery [19,20]. In this study, family support and cognitive function in acute stroke patients were significantly correlated, which can be interpreted to mean that family support can enhance the recovery of a patient from both physical dysfunction and cognitive dysfunction based on the belief and trust gained from those around him.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Patients and caregivers also reported that memory problems after a stroke negatively affected their daily life and emotions. 18 If risk of future cognitive problems are not identified during the acute hospital stay they may not come to medical attention until there is a crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Living with memory deficits may result in negative effects on the PpS and their family once in the community such as fragmented care, marginalisation and lack of proactive follow-up [ 29 ]. A recent systematic review and meta-ethnography found that PpS and carers may feel abandoned by healthcare services due to lack of continuity of care, limitations in access to services and inadequate information and opportunity to re-engage with services [ 30 ].…”
Section: Introductionmentioning
confidence: 99%